Neurological manifestations of nontuberculous mycobacteria in adults: case series and review of the literature - Mina, Yair; Kline, Ahnika; Manion, Maura; Hammoud, Dima A.; Wu, Tianxia; Hogan, Julie; Sereti, Irini; Smith, Bryan R.; Zerbe, Christa S.; Holland, Steven M.; Nath, Avindra (Frontiers in Neurology, 2024)
Introduction: Nontuberculous mycobacteria (NTM) mediated infections are important to consider in cases with neuroinflammatory presentations. We aimed to characterize cases of NTM with neurological manifestations at the National Institutes of Health (NIH) Clinical Center and review the relevant literature.Between January 1995 and December 2020, six cases were identified. Records were reviewed for demographic, clinical and radiological characteristics. A MEDLINE search found previously reported cases. Data was extracted followed by statistical analysis to compare two groups (cases with slow growing mycobacteria (SGM) versus those with rapidly growing mycobacteria (RGM)) and evaluate for predictors of survival. NIH cases were evaluated for clinical and radiological characteristics. Cases from the literature were reviewed for differences between SGM and RGM cases and to identify predictors of survival.Results: Six cases from NIH were identified (age 41±13, 83% male). Five cases were caused by SGM (Mycobacterium avium complex (MAC) n=4; Mycobacterium haemophilum n=1) and one due to RGM (Mycobacterium abscessus). Underlying immune disorders were identified only in the SGM cases (genetic (n=2), HIV (n=1), sarcoidosis (n=1), anti-interferon-gamma antibodies (n=1)). All cases were diagnosed by tissue analysis. Literature review found 81 reports on 125 cases (SGM n=85, RGM n=38, non-identified n=2). No immune disorder was reported in 26 cases (21%). Within SGM cases, the most common underlying disease was HIV infection (n=55, 65%) and seizures and focal lesions were more common. In RGM cases, the most common underlying condition was neurosurgical intervention or implants (55%), and headaches and meningeal signs were common. Tissue-based diagnosis was used more for SGM than RGM (39% vs. 13%, p=0.04). Survival rates were similar in both groups (48% SGM and 55% in RGM).Factors associated with better survival were a solitary CNS lesion (OR 5.9, p=0.01), and a diagnosis made by CSF sampling only (OR 9.9, p=0.04).Discussion: NTM infections cause diverse neurological manifestations, with some distinctions between SGM and RGM infections. Tissue sampling may be necessary to establish the diagnosis and an effort should be made to identify an underlying immune disorder.